2021
DOI: 10.1088/2058-6272/abf423
|View full text |Cite
|
Sign up to set email alerts
|

UV and soft x-ray emission from gaseous and solid targets employing SiC detectors

Abstract: A ns Nd:YAG pulsed laser has been employed to produce plasma from the interaction with a dense target, generating continuum and UV and soft x-ray emission depending on the laser parameters and target properties. The laser hits solid and gaseous targets producing plasma in high vacuum, which was investigated by employing a silicon carbide detector. The two different interaction mechanisms were studied, as well as their dependence on the atomic number. The photon emission from laser-generated plasma produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…behind a light absorber. This effect cannot be seen by SiC detectors, even to thinner surface metallizations or interdigitated metallizations, due to their greater energy gap, which produces background only for UV and X-ray detection but not for visible radiation, in agreement with the literature [20][21][22].…”
Section: Jinst 19 P07005supporting
confidence: 85%
“…behind a light absorber. This effect cannot be seen by SiC detectors, even to thinner surface metallizations or interdigitated metallizations, due to their greater energy gap, which produces background only for UV and X-ray detection but not for visible radiation, in agreement with the literature [20][21][22].…”
Section: Jinst 19 P07005supporting
confidence: 85%
“…Such spectra and ionization potentials of the ion charges indicated that the plasma temperature increases with the atomic number of the target, literature data reporting that the plasma temperature increases with the plasma electron density, i.e., with the atomic number of the irradiated target [8]. The evaluated plasma temperatures, not directly measured, but only approximated by the above considerations, have been reported as a function of the atomic number of the laser irradiated targets, as reported in Fig.…”
Section: Resultsmentioning
confidence: 68%
“…At this intensity, nanosecond (ns) lasers can be employed for different applications, such as for hot plasma generation in the vacuum, ion source production, ion acceleration and post-acceleration, thin-film deposition, X-ray production, production of nanoparticles in liquids, polymers welding, thermal treatments of surfaces, induction of oxidation and reduction processes in different materials, and others [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The detection efficiency of such detectors is only limited by their thickness and absorption in the contact film on the input window, thus uncovered surfaces can be employed to reveal UV and low energetic ions [12]. Moreover, SiC detectors have been used with active region depth from some microns up to 80 microns, to detect low energy and high energy ions and soft and hard X-rays, respectively [13,14].…”
Section: Introductionmentioning
confidence: 99%